Traditional Practices Influence Student’ Motivation at School and in School Athletics in the Republic of Benin - EDOH, KOFFI PIERROT (My University, 2013)
In their daily activities, men are influenced by various factors. These factors, which can be environmental, social and/or cultural, vary according to the types of activities in which these people are engaged. For the Beninese, everything has meaning, which is why, they regularly practice their traditional cultural heritage, as it strengthens their morale during professional activities. Students from this environment can not escape this reality. Therefore, they do not hesitate to call on traditional, cultural practices to manage stress more effectively and increase their motivation. The results of two questionnaires that were administered to 271 non-sports students and to 138 student athletes, revealed that the Beninese traditional cultural practices (prayers, charms and offerings), are making their entry to school and into school athletic associations. The presence of such practices in secondary schools varies between rural and urban students and between animist, Christian and Muslim students.
Keywords: Traditional practices; Stress; Motivation; School; Sport